IMPLEMENTASI ELECTRONIC COSTUMER RELATIONSHIP MANAGEMENT (E-CRM) SEBAGAI SISTEM INFORMASI DALAM PENINGKATAN LAYANAN PESERTA DIDIK DI BIMBEL EXPRESS BERBASIS CRM TOUCHING APPLICATION - dian lesmana; Fahmi Yusuf; dede Irawan (Cloud Information, 2019)
Non-formal education is an every opportunity where there is regular and directed communication outside of school, where a person gets information, knowledge, training or guidance according to his age and life needs with the aim for developing the level of skills, attitudes of participant that is efficient and effective in the family and even the community and country. In Indonesia, education is placed as a must for every Indonesian citizen. However, the current non-formal education is less popular. It can be identified with the number of existing unemployment, this will have a bad impact if it is left unchecked ("Education Observer, Darmaningtyas friday (3/4) Jakarta, kompas.com). This makes most non-formal educational institutions in Indonesia, especially EXPReSS, finds difficulty to get students, therefore the solution that is considered appropriate for this problem is CRM Operations. The purpose of this study is to apply the Customer Relationship Management (CRM) method in the Student Service Information System guided by EXPReSS, where the application of Operational Customer Relationship Management (CRM) is applied to the chat, discount, online registration and academic information functions to facilitate students in obtaining information and satisfying service. So that the relationship between the tutoring and students can be better. This information system is made in web-based, using the PHP programming language and MySQL as its database.